Process parameters optimization and microstructure evaluation on friction spot-welded aluminum/copper dissimilar joints - Cardillo, Maria Eduarda Barbosa (2016)
Dissimilar materials welding is a field of increasing interest for a wide range of industrial applications. Specifically, the welding of aluminum alloys with copper has potential applications in the heating, ventilation and air conditioning (HVAC) industries, being used for the production of electrical and thermal connections. However, these applications require the development of reliable, efficient and economic welding processes. Mismatches between the material’s physical properties and metallurgical factors make the identification of an adequate welding process and parameters a challenge to be overcome. In the present research work, friction spot welding (FSpW) was applied to create welded joints between AA5083-O and phosphorus-deoxidized copper. The objectives were: to optimize the process parameters and to determine the dominant factors by means of design of experiments; to comprehend the microstructure formation mechanism; and to determine the fracture behaviors of the welds under shear loading. For these purposes, mechanical testing and metallographic analyses were used to evaluate the welded joints. Lap-shear strength was chosen to determine the weld quality and microhardness tests were done in order to better understand the specific local mechanical resistance of the different welding zones. Microstructural analyses were performed by means of optical microscopy, scanning electron microscopy, energy dispersive spectroscopy and by the electron backscatter diffraction technique. The software Thermocalc was also used to theorize the intermetallic formation. The results confirmed the effectiveness of the FSpW technique when applied to weld the dissimilar metals Al and Cu. The plunge depth welding parameter was determined statistically as the dominant factor in Al and Cu friction spot-welded joints. Mainly, due to its effect on the formation of a deformed metallic volume just below the interface. Microscopically, two intermetallic compounds were identified across the interface and micro-constituents with characteristics of an eutectic structure were also observed in some welding conditions. This metallurgical feature is detrimental to the mechanical properties, and therefore must be controlled.